Epidemiological aspect and major constraints in controlling haemorrhagic septicemia in dairy animals of Punjab - MALIK, M H; VERMA, H K (The Indian Journal of Animal Sciences, 2018)
Present study was undertaken to study the epidemiological aspect of haemorrhagic septicemia (HS) in dairy animals and various constraints in controlling its occurrence in different agro-climatic zones of Punjab. The study was conducted in all the different agro-climatic zones of Punjab by multistage stratified random sampling of 720 dairy farmers and categorized them on the basis of herd size of dairy animals, viz. small (5–10), medium (11–50) and large (>50). The overall incidence and case fatality rate (CFR) of HS among dairy animals was 5.45 and 45.15% respectively. Incidence risk of HS on the species basis varied significantly and was observed highest in buffaloes (6.27%), followed by crossbred (4.67%) and indigenous cattle (3.91%). Within different herd sizes, the incidence risk of HS varied significantly and was highest in small herd size (10.52%) followed by medium (5.44%) and large herd size (3.01%). Incidence risk varied significantly between the different agro-climatic zones of Punjab within small and large sized herds but not in medium sized herds. CFR among the different herds was highest in small herd (49.28%) followed by medium herd (44.32%) and large herd (39.15%). The major constraints faced by farmers for controlling HS estimated by using Garrett’s ranking technique included failure of prophylactic vaccination, cost of treatment, strict biosafety measures and hygienic sanitary conditions not followed, inadequate early disease detection and poor availability of veterinary and extension services. Various veterinary and extension tools should be chosen based on agro-climatic conditions and analyzing farmers in respect of education, herd size, extension contacts, teledensity and training etc. to overcome this dreadful disease of dairy animals.